Analysis of Darcy-Forchheimer flow of magnetized hybrid nanofluid (MoS2+ZnO/E) with non-linear heat source and quartic autocatalytic chemical reaction - Riaz, Muhammad; Khan, Nargis; Hashmi, M. S.; Tawfiq, Ferdous M.; Bilal, Muhammad; İnç, Mustafa (Taylor & Francis Inc, 2026)
In this article, an effort is made to analyze the 3-D flow of hybrid nano-fluid over a rotating stretching sheet. The hybrid nanofluid contains engine oil as a base fluid amalgamated with nano-particles MoS2 and ZnO:The flow is assumed to pass through a Darcy-Forchheimer medium subjected to the influence of an inclined magnetic field. In addition, heat radiation, Joule heating, viscous dissipation, nonlinear heat source, and quartic auto-catalytic chemical reaction are applied to discourse heat and mass transfer features. The PDEs representing the physical problem are converted to ODEs with the introduction of similarity transformations. The solution of the problem is determined numerically by using MATLAB built-in bvp4c method. The proposed mathematical model's validation is ascertained by comparing it with an earlier study in limiting case. In this regard, an excel-lent consensus is accomplished. The current investigation reveals that the flow along axial direction gets retarded by enhancing the values of rotational parameter, inertial parameter, and magnetic parameter, whereas the flow along radial direction gets accelerated. The increasing value of angle of inclination admirably resists the motion of nanofluid and hybrid nano-fluid. The concentration profile gets decreased under the increasing influence of inclination angle and Schmidt number while it enhances for homogeneous reaction parameter. The enhancing values of rotational parameter, solid volume fraction and temperature, and exponential depend-ent heat generation parameters enhance the value of Nusselt number.
Keywords: Autocatalytic chemical reaction; bvp-4c; Darcy-Forchheimer flow; hybrid nanofluid; inclined magnetic field; non-linear heat source